Morphometric Analysis of Mount Ararat (Eastern Anatolia, Türkiye) - Avci, Vedat; Sunkar, Murat; Toprak, Ahmet (My University, 2022)
In this study, the morphometric characteristics of Mount Ararat which is a strato-volcano are analyzed. Türkiye’s highest Mountain, Mount Ararat, is located in Eastern Anatolia. The Mountain takes the shape of two major volcanic cones after 2500 m height; these volcanic cones are named Greater Mount Ararat (5137 m) and Little Mount Ararat (3896 m). In this study, relief morphometry, basin morphometry, and drainage characteristics are morphometrically analyzed with Geographic Information Systems (GIS) using 10x10 m resolution Digital Elevation Model (DEM). According to the analysis results, there is an increase in the elevation on the high and steep slopes of the main cone and the slope values increase up to 56° in some locations towards the summit. On the other hand, according to the aspect analyses, 19.9% of slope faces are north-east direction, 14.7% of the slopes are north-direction, 9.4% are northwest, 9.8% are west, 10.7% are southeast, and 16.4% of the slopes are east direction. These results support the fact that Mount Ararat extends in NW-SE direction and is formed on the basis of a fault line in this direction. According to the grouping made by the altitude ranges analysis, the decrease in the rate of elevation belts starting from the slopes of the mountain towards the top confirms the structure of volcanic cone. Elevation differences in relative relief analyses range between 0 and 1141 m and this value increases to 1141 m on the slopes surrounding the summit. The cone structure of Mount Ararat was prominent in transverse and longitudinal profile analyses.
Keywords: Coğrafya; Jeoloji